Regiocontrolled Ruthenium-Catalyzed Isomerization of Propargyl Alcohols - Skowaisa, Steffen; Haak, Edgar (Synlett, 2024)
A diaminocyclopentadienone ruthenium complex allows control of regioselectivity in the ruthenium-catalyzed isomerization of propargyl alcohols through the choice of additive. Thereby, both products of the Meyer–Schuster rearrangement and redox isomerization products are selectively accessible. In the presence of hydroxylamine-O-sulfonic acid, unsaturated nitriles are formed instead. The ruthenium catalyst is readily available and stable to moisture, air, and acidic conditions.
Keywords: ruthenium; Meyer–Schuster rearrangement; redox isomerization; unsaturated nitriles; propargyl alcohols